The Effect Perceived Organizational Support on Employee Performance: The Mediating Role of Employee Engagement At PT Pegadaian Syariah CPS Babakan - Ahmad Diya’ Ulhaq Al Harisi; Andre Dwijanto Witjaksono (International Journal of Social, Economic, and Business, 2025)
This research aims to test and analyze he influence of Perceived organizational support on employee performance through employee engagement at pt Pegadaian syariah cps Babakan. This research uses a quantitative methods. The sampling technique used is non-probability sampling with a saturated sample, in which the entire population is used as the sample with 54 respondents. Data were analyzed using partial least squares (PLS) with the smartpls 3.0 software. The results show that Perceived organizational support has a positive and significant effect on employee performance. Perceived organizational support also has a positive and significant effect on employee engagament. Furthermore, employee engagement has a positive and significant effect on employee performance. The path analysis further reveals that employee engagement functions as a mediating variable in the relationship between Perceived organizational support and employee performance.